Match-play, training workloads and sensorimotor and neuromuscular performance of elite young soccer players - Clancy, C.; Gleeson, N.; Mercer, T. (Scientific Journal of Sport and Performance, 2023)
Purpose: The purpose of this study was to assess sensorimotor and neuromuscular performance capabilities over an in-season microcycle in early-career professional soccer players and to examine the relationship with training and match-play workload. Methods: Sensorimotor and neuromuscular performance capabilities (isometric knee extensor: force replication error, peak force, electromechanical delay, rate of force development) of 12 professional soccer players were assessed over a 7-day period. Training and match-play workload was also recorded over the same period for each player (high-intensity running distance). Fluctuations in sensorimotor and neuromuscular performance and workload variables were analysed. Results: There was evidence of fluctuations in sensorimotor and neuromuscular performance capability over the microcycle that reached statistical (p < .005) and practical (18.1% [baseline-to-peak]) significance alongside heterogeneity in training and match workload (264% [coefficient of variation], p < .0005). Some temporal congruence among fluctuating patterns of intra-microcycle training and match-play load and concomitant electromechanical delay performance was noted (p < .005). Asynchronous responses were observed for peak force, but rate of force development and force replication error capabilities were unchanged during the microcycle. Conclusion: While some neuromuscular performance capabilities fluctuate over an in-season microcycle and are influenced partially by high-intensity running workload, sensorimotor performance capabilities were unchanged during the microcycle.